Influence of microwave heating on the microstructures of iron ore pellets with coal during reduction. (9th August 2017) - Chun, T.; Long, H.; Di, Z.; Wang, P.; Meng, Q.
Abstract : Iron ore oxidised pellets as the burden of blast furnace present many advantages, such as uniform size, high iron grade and high physical strength. A comparison of the iron ore oxidised pellets with coal (out-proportioning) by conventional heating and microwave heating was carried out in this paper. Microstructure transformations during reduction process were investigated by optical microscopy and scanning electron microscope with energy dispersive spectrometry analysis. Micro-hardness of metallic iron phase formed in the reduction was tested with digital micro-hardness tester. The influences of microwave heating on reduction degree, morphology, iron phase and gangues were investigated, respectively. The results show that reduction time can be greatly shortened by microwave heating even at lower temperatures. The fine cracks generated, as the pellets were heated by microwave, were irradiated due to the selectivity of microwave heating. Densification of the metallic iron phase and the separation of the iron and gangues were both found to be enhanced by microwave heating.